The A to Z of Alzheimer's disease - Turkington, Carol; Mitchell, Deborah R.; Turkington, Carol (New York : Checkmark Books, 2010)
Discusses the disease, its causes and symptoms, related health conditions, treatment options, research, and social issues related to Alzheimer's.
Previously published as: Encyclopedia of Alzheimer's disease.
Includes bibliographical references (p. 264-284) and index.
Keywords: Alzheimer's Disease -- Encyclopedias -- English